2017
DOI: 10.1590/s1678-9946201759054
|View full text |Cite
|
Sign up to set email alerts
|

Sandfly fauna (Diptera: Psychodidae) in an urban area, Central-West of Brazil

Abstract: Biological and ecological relations among vectors and their pathogens are important to understand the epidemiology of vector-borne diseases. Camapuã is an endemic area for visceral and tegumentary leishmaniasis. The aim of this study was to characterize the sandfly fauna present in Camapuã , MS, Brazil. Sand flies were collected every fortnight from May 2014 to April 2015 using automatic light traps in the domicile and peridomicile of twelve neighborhoods and forest. The collected specimens were identified bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…The overall number of males was higher than females, as reported in different studies conducted in other regions of Brazil [3538]. It is acknowledged that the sex ratio may be influenced by trapping methods, with light traps usually attracting more males than females [39].…”
Section: Discussionmentioning
confidence: 89%
“…The overall number of males was higher than females, as reported in different studies conducted in other regions of Brazil [3538]. It is acknowledged that the sex ratio may be influenced by trapping methods, with light traps usually attracting more males than females [39].…”
Section: Discussionmentioning
confidence: 89%
“…[47], and Fernandes et al . [71]. No periodicity was observed for rainfall, and sand fly frequency did not correlate significantly with this variable.…”
Section: Discussionmentioning
confidence: 96%
“…Evandromyia aldafalcaoae , a species restricted to Mato Grosso do Sul, has been frequently collected from disturbed environments—peridomestically in the Pantanal sub-region of Nhecolândia [67] and in Corumbá county [47, 55], as well as indoors [65, 68]. Nyssomyia whitmani , a vector of etiological agents of cutaneous leishmaniasis in several Brazilian localities, has been frequently reported from Mato Grosso do Sul, especially where outbreaks of tegumentary leishmaniasis have occurred [61, 69, 70, 71].…”
Section: Discussionmentioning
confidence: 99%
“…cruzi abundance and climatic variables showed no significant statistical association [ 24 , 27 , 59 ]. However, it was observed that the species occurs throughout the year, with population peaks in the months with high temperature [ 21 , 24 , 27 , 59 ]. These previous studies considered both male and female specimens of L .…”
Section: Discussionmentioning
confidence: 99%